Correlates and predictors of homonegativity among Mexican medical students - José Moral de Rubia; Adrián Valle de la O (Interacciones)
Background: The internalization of cultural homophobia as a rejection toward any internal and interpersonal aspect related to homosexuality can lead to intrapsychic conflicts and discrimination. This phenomenon when manifested in health professionals can lead to the violation of the rights of patients and colleagues. This research aims to identify the correlates and predictors of homonegativity in medical students. Method: A convenience non-probability sampling was used. A self-report questionnaire composed of questions on socio-demographic information, sexual orientation, and 18 scales of assessment was applied, including the 16-item Homonegativity scale (HN-16). Results: The sample was composed of 202 volunteer participants, who were studying at a private medical school in Monterrey, Mexico. A principal component analysis was performed with scales of assessment that were correlated with HN-16 total score, and yielded three components: masculinity-harshness-externality, religiosity-conservatism, and homosexuality-chivalry-honesty. These three components explained 35.4% of the variance of HN-16 total score through multiple linear regression. Conclusion: Greater flexibility in traditional gender roles, lower religious radicalism, lower conservatism and ethical values based on empathic understanding, respect and personal responsibility reduce homonegativity.